Transformasi Diri dan Harmonisasi Alam dengan Puasa: Perspektif Al-Qur'an dan Sains - Abdullah Safei; Ahmad Syukron; Iwan Satiri; Muhammad Irawan Taqwa (Jurnal Studi Al-Qur'an, 2025)
Contemporary society often experiences stress, anxiety, and depression due to technological advances and rapid social change. In the Qur'an, Surah Al-Baqarah/2: 183, fasting is described as a comprehensive practice that helps individuals cope with stress and improve mental health through reflection and changes in existential awareness. This study aims to explore self-transformation and harmony between humans and nature through fasting, using approaches from the Qur'an and science. The method used is qualitative descriptive analysis, utilizing relevant literature on fasting, mental health, and human interaction with the environment. The research findings indicate that fasting is a spiritual ritual and teaches simplicity and respect for nature, which supports the balance between humans and the environment. The recommendations from this study are to encourage the practice of fasting to achieve better mental and ecological health, and to expand studies on the impact of fasting in the context of mental health and the environment.